Impact of gender dichotomy on dividend payout policy in listed Nigerian financial services firm - Damilola Felix Eluyela; Olajide Dahunsi; Olawumi Ajoke Tolase; Wisdom Okere; Mautin Arinola Ogabi; Abiola Kafidipe (Cogent Business & Management, 2019)
This paper examines the impact of gender dichotomy on dividend payout policy in listed Nigerian financial services firm. A random-panel data methodological approach underpins this study. The study observed an overall panel data of 248 firm-year observations drawn from the sample of 31 financial service firms listed in Nigeria stock exchange between 2010-2017. The findings from the random-panel data regression adopted for the study shows that the presence of female directorship does not significantly influence dividend payout in Nigeria. The rate of dividend payout is highly determined by firm age and their performance. However, we recommend a more diverse board structure, considering the significant effect board size has on dividend payout policy. A more robust and diverse board will create an atmosphere of discipline and control in the organization.
Keywords: G21; G35; M41; 650; board size; diversity; dividend payment; gender; panel data; personal traits